2023
DOI: 10.3389/fmicb.2023.1160631
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus form affects the advantages that arbuscular mycorrhizal fungi confer on the invasive plant species, Solidago canadensis, over its congener

Abstract: Interactions between plants and arbuscular mycorrhizal fungi (AMF) are strongly affected by soil phosphorus (P) availability. However, how P forms impact rhizosphere AMF diversity, community composition, and the co-occurrence network associated with native and invasive plants, and whether these changes in turn influence the invasiveness of alien species remain unclear. In this work, we performed a greenhouse experiment with the invasive species Solidago canadensis and its native congener S. decurrens to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The abundance of Claroideoglomus was greater in AMF communities colonizing the roots of carrots grown in high-vs. low-phosphorus soils. A recent study by Chen et al (2023) also reported the effects of soil phosphorous (adenosine monophosphate applied at 20 mg kg −1 soil) and host species on AMF communities detected in the roots of the perennial herbs Solidago canadensis L. and S. decurrens, compared to soil with no phosphorus applied in a greenhouse study. The application of phosphorus increased the relative abundance of Claroideoglomeraceae, and decreased Acaulosporaceae in AMF communities colonizing the roots of S. decurrens (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The abundance of Claroideoglomus was greater in AMF communities colonizing the roots of carrots grown in high-vs. low-phosphorus soils. A recent study by Chen et al (2023) also reported the effects of soil phosphorous (adenosine monophosphate applied at 20 mg kg −1 soil) and host species on AMF communities detected in the roots of the perennial herbs Solidago canadensis L. and S. decurrens, compared to soil with no phosphorus applied in a greenhouse study. The application of phosphorus increased the relative abundance of Claroideoglomeraceae, and decreased Acaulosporaceae in AMF communities colonizing the roots of S. decurrens (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 98%
“…(2023) also reported the effects of soil phosphorous (adenosine monophosphate applied at 20 mg kg −1 soil) and host species on AMF communities detected in the roots of the perennial herbs Solidago canadensis L. and S. decurrens , compared to soil with no phosphorus applied in a greenhouse study. The application of phosphorus increased the relative abundance of Claroideoglomeraceae, and decreased Acaulosporaceae in AMF communities colonizing the roots of S. decurrens ( Chen et al., 2023 ). In contrast, application of phosphorus increased the relative abundance of Glomeraceae, and decreased the abundance of Diversisporaceae and Acaulosporaceae in S. canadensis ( Chen et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased phosphorus content can reduce the competitive ability of invasive Solidago canadensis under high nitrogen conditions (Wan et al, 2018). On the other hand, depending on the phosphorus form, its availability in the soil can also play a key role in mediating interactions between goldenrods and soil microorganisms such as mycorrhizal fungi, thus enhancing goldenrod invasion (Chen et al, 2023).…”
Section: Importance Of Environmental and Anthropogenic Variablesmentioning
confidence: 99%